2006
DOI: 10.1080/j157v06n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Peony Root Extract on the Large Conductance Calcium-Activated Potassium Current Essential in Production of Bursting Activity

Abstract: To elucidate the mechanism of inhibitory action of peony root extract on pentylenetetrazol-induced bursting activity, effects of peony root extract on the iberiotoxin-sensitive large conductance calcium-activated potassium (BKCa) current that plays an essential role in the production of bursting activity were investigated. Peony root extract showed a clear inhibitory effect on the iberiotoxin-sensitive calcium-activated potassium current. Peony root extract also showed clear inhibitory effects on spontaneous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A previous study demonstrated the inhibitory effect of paeoniflorin extract on PTZ-induced EEG power spectrum changes and suggested that paeoniflorin had anticonvulsant activity [90]. The anticonvulsant effects of paeoniflorin may primarily be associated with the inhibitory effects of peony root extract on the large conductance calcium-activated potassium current essential in the production of bursting activity [91,92] and its protective effects on neuron damage in the hippocampus induced by the cobalt focus epilepsy model [90]. One recent study demonstrated the anticonvulsant effect of paeoniflorin on experimental febrile seizures in immature rats and suggested the potential application for febrile seizures in children [93].…”
Section: Paeonia Lactiflora (Chishao)mentioning
confidence: 96%
“…A previous study demonstrated the inhibitory effect of paeoniflorin extract on PTZ-induced EEG power spectrum changes and suggested that paeoniflorin had anticonvulsant activity [90]. The anticonvulsant effects of paeoniflorin may primarily be associated with the inhibitory effects of peony root extract on the large conductance calcium-activated potassium current essential in the production of bursting activity [91,92] and its protective effects on neuron damage in the hippocampus induced by the cobalt focus epilepsy model [90]. One recent study demonstrated the anticonvulsant effect of paeoniflorin on experimental febrile seizures in immature rats and suggested the potential application for febrile seizures in children [93].…”
Section: Paeonia Lactiflora (Chishao)mentioning
confidence: 96%
“…These food types also contribute to the promotion of self-medication, i.e., the use of over-the-counter medicines, including herbal and traditional products, to treat self-recognized illnesses or symptoms (1,2). Of particular interest is the biological activity and safety of natural products, including food, traditional herbs, kampo and their phytochemicals (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%